Effect of spinal anesthesia on the ratio of agreement between the lower and upper extremity pressures in lower abdominal surgeries - Mehdi Taybi arasteh; Paiman Rezagholy; Hamid Tawana; Daem Roshani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2018)
Background: During spinal anesthesia, blood pressure is often measured indirectly through inflating a cuff at the arm. However, the measurement of blood pressure at the arm is sometimes not possible due to the presence of burns and implementation of orthopedic or plastic surgery on the upper limb. In these cases, lower extremity blood pressure should be measured.